Communities and ecosystems : linking the aboveground and belowground components - Wardle, David A., 1963- (Princeton University Press, 2002)
Most of the earth's terrestrial species live in the soil. These organisms, which include many thousands of species of fungi and nematodes, shape aboveground plant and animal life as well as our climate and atmosphere. Indeed, all terrestrial ecosystems consist of interdependent aboveground and belowground compartments. Despite this, aboveground and belowground ecology have been conducted largely in isolation. This book represents the first major synthesis to focus explicitly on the connections between aboveground and belowground subsystems--and their importance for community structure and e.
Keywords: Soil ecology.; Food chains (Ecology); Soil; Food Chain; Écologie du sol.; Chaînes alimentaires (Écologie); NATURE -- Ecology.; NATURE -- Ecosystems & Habitats -- Wilderness.; SCIENCE -- Environmental Science.; SCIENCE -- Life Sciences -- Ecology.; SCIENCE -- Life Sciences -- Biology.; Soil ecology; Bodenökologie; Nahrungskette; Ecosystemen.; Biosfeer.